2016
DOI: 10.1038/ncomms11211
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of a native ferroelectric metal

Abstract: Over 50 years ago, Anderson and Blount discussed symmetry-allowed polar distortions in metals, spawning the idea that a material might be simultaneously metallic and ferroelectric. While many studies have ever since considered such or similar situations, actual ferroelectricity—that is, the existence of a switchable intrinsic electric polarization—has not yet been attained in a metal, and is in fact generally deemed incompatible with the screening by mobile conduction charges. Here we refute this common wisdom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 43 publications
3
97
0
Order By: Relevance
“…In figures 2 and S1 one should also remark the presence of cation-oxygen relative z-displacements in the SRO electrodes, for the 9-and 7-PTO structures, which are driven by the ionic relaxations in the dielectric at interfaces. These ionic displacements, larger at interfaces and decreasing inside the electrode, as well as the cubic to tetragonal distortion of the SRO unit cell show that a polar state may onset in the metallic phase at the interface with a ferroelectric, in agreement with previous results, [7,84]. The phenomenon has been explained by the softness of the metallic oxide lattice, which allows the ferroelectric displacements in PTO to penetrate into the metal electrode, acting toward the stabilization of a ferroelectric phase in a narrow region at the interface [7].…”
Section: Structural Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In figures 2 and S1 one should also remark the presence of cation-oxygen relative z-displacements in the SRO electrodes, for the 9-and 7-PTO structures, which are driven by the ionic relaxations in the dielectric at interfaces. These ionic displacements, larger at interfaces and decreasing inside the electrode, as well as the cubic to tetragonal distortion of the SRO unit cell show that a polar state may onset in the metallic phase at the interface with a ferroelectric, in agreement with previous results, [7,84]. The phenomenon has been explained by the softness of the metallic oxide lattice, which allows the ferroelectric displacements in PTO to penetrate into the metal electrode, acting toward the stabilization of a ferroelectric phase in a narrow region at the interface [7].…”
Section: Structural Resultssupporting
confidence: 92%
“…The phenomenon has been explained by the softness of the metallic oxide lattice, which allows the ferroelectric displacements in PTO to penetrate into the metal electrode, acting toward the stabilization of a ferroelectric phase in a narrow region at the interface [7]. More recently, Filippetti et al reported that Bi 5 Ti 5 O 17 complies with the sufficient symmetry requirements for a switchable polarization to exist and the material can sustain a sizeable potential drop along the polar direction, in spite of being a metal [84]. However, in the present case the results do not reveal the presence of a ferroelectric polarization in the SRO electrodes, as discussed further.…”
Section: Structural Resultsmentioning
confidence: 99%
“…In 2014, Xiang proposed that the polarization may be controlled by the electric field if the current flow perpendicular to the slab is blocked [18]. Similarly, Filippetti et al [19] and Luo et al [20] predicted the possibility of a polarization reversal in Bi5Ti5O17 layers and two-dimensional (2D) CrN, respectively. Very recently, Fei et al…”
Section: Main Textmentioning
confidence: 99%
“…However, in the "FE metal" case, if one contacts metallic film with electrodes, there will be a current flow and no electric field will be effectively applied. In practice, to apply electric fields to metallic films, one needs to grow some buffer insulating layers [18,19], or straightly bring electrodes/charges to the proximity of a free-standing film [18]. As a reference, in our calculation, the dipole layer that generates the external fields considered here (810 9 V/m) has a surface dipole moment density of 3.3810 -11 C/m, which amounts to a polarization charge of 7.0810 -2 C/m 2 .…”
Section: (A)mentioning
confidence: 99%
“…Superconductivity requires free carriers, with the superconducting energy gap depending strongly on the density of states at the Fermi level, while free charges tend to rapidly screen electric dipole fields and prevent longrange spontaneous electric polarization. Indeed, only recently have long-sought examples of so-called "polar metals" been discovered [6][7][8][9]. Because of this discordance, the fundamental relationship between ferroelectricity and superconductivity in SrTiO 3 is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%